The Anti-Biofouling Effect of Piper Betle Extract on Membrane Biofouling in Bioreactor for Batik Wastewater Treatment - Muhammad Faisal, Siddiqui (2012)
Navigating novel biological route to mitigate biofouling is of great worth in order to allow sustainable performance of MBRs in wastewater treatment technology. Recently, it was confirmed that a number of natural compounds in plants have an anti-biofouling effect, reducing the formation of biofilm. The main objectives of this study were to investigate the anti-biofouling effects of Piper betle extract (PBE) on membrane biofouling and how PBE mitigates biofouling based on quorum sensing (QS). Membrane biofouling propensity was investigated for a bacterial consortium and bacterial strains of batik wastewater. During MBR operation with bacterial consortium, a significant relationship (R2= 0.9916) between extracellular polymeric substances (EPS) and transmembrane pressure (TMP) was revealed. MBR showed increased removal performance for dye and chemical oxygen demand (COD) removal with operation time. Fourier transform infrared spectroscopy (FTIR) showed the presence of EPS in membrane foulants. Furthermore, scanning electron microscopy (SEM) confirmed the occurrence of biofouling. The microtiter plat assay suggested that strain FS5 to be the major biofilm contributor. Batch tests of the production of EPS indicated that the Bacillus strain (FS5) produced a large amount of EPS compared to the bacterial consortium. This study addressed the feasibility of Piper betle extract (PBE) as anti-biofouling agent against the model organism Pseudomonas aeruginosa PAO1 and bacterial consortium. The anti-biofouling effects of PBE were evaluated via a microtiter plate assay; changes in the growth rate (µ) and EPS production. SEM was employed to qualitatively illustrate the biofilm formation. The anti-biofouling effects of PBE revealed 80 % reduction in biofilm formation, growth rate (87%) and reduced the EPS production. Furthermore, it decreased the soluble EPS concentration, reduced the cake resistance, and a two-fold increase in time required to reach 33 kPa of TMP. The PBE indicated a negligible effect on endogenous decay rate and biomass yield. SEM of sludge particles in PBE bioreactor showed the presence of a mixture of bacteria on its surface with a clear spherical shaped boundary. Besides that PBE indicated negligible effects on biological treatment performance. Response surface methodology (RSM) has been employed to mitigate EPS, TMP rise-up control, and dye removal in ultrafiltration MBR. The optimum conditions found to be biofouling reducer (BFR) of 0.23 mg/mg MLSS, HRT of 30.16 h and air flow rate of 0.60 l/min, with predicted values as 28.28 mg/l of EPS, 24.16 kPa of TMP and 95.65% dye removal, respectively. Validatory tests were closely agreed with the predicted values. The autoinducers production in bioreactor was confirmed using an indicator strain Agrobacterium tumefaciens. Moreover, three different AHLs were found in biocake using thin layer chromatographic analysis. An increase in EPS and TMP was observed with AHL activity of the biocake during continuous MBR operation, which shows that membrane biofouling was in close relationship with QS activity. PBE was verified to mitigate membrane biofouling via inhibiting AHLs production. These results exhibited that PBE could be a novel agent to target AHLs for mitigation of membrane biofouling based QS.